CONTROL AND SUPERVISION OVER THE IMPLEMENTATION OF MEASURES FOR INTERCEPTION OF COMMUNICATIONS - THE MACEDONIAN CASE - Ilijevski, Ice; Krstevska Savovska, Katerina (NBP. Nauka, bezbednost, policija, 2021)
e implementation of the measures for interception of communications is a useful toolin ghting organized crime and endangering public and national security. However, if they are notin accordance with the law, their implementation can seriously jeopardize the privacy of individuals.In the past, there had been several Macedonian a airs related to the illegal surveillance of communicationthat caused reformation of the system for interception of communications. erefore,if certain inconsistencies are timely detected and signalized by the representatives of the controland supervising bodies, then there should be an adequate reaction for protection of the generalvalues of the democratic society. Having in mind the above, the paper will give an overview of thecurrent Macedonian situation regarding the system of control and supervision of the measures forinterception of communications, or to be more precise - it will analyse the institutions and bodiesthat have authority to control and supervise. A special emphasis will be given to the de cienciesand weaknesses of this system, as well as the necessity for its upgrading and improving in order toprevent possible abuses in the future.